1999
DOI: 10.1002/(sici)1098-2264(199912)26:4<304::aid-gcc4>3.0.co;2-1
|View full text |Cite
|
Sign up to set email alerts
|

Dominant genetic alterations in immortalization: Role for 20q gain

Abstract: Gain of 20q has been observed in many cancer types, including bladder cancers. However, the biological significance of low‐copy‐number 20q gain in human cancer pathogenesis has not yet been defined. We reported that immortalization of human uroepithelial cells (HUC) transformed with human papillomavirus 16 (HPV 16) E7 is associated with single‐copy 20q gain (P = 2 × 10‐7). We also observed 20q13.2 amplification in some cell lines, but only after 20 passages. Thus, we hypothesized that low‐copy gain of 20q gene… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

3
18
0

Year Published

2000
2000
2016
2016

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 46 publications
(21 citation statements)
references
References 29 publications
3
18
0
Order By: Relevance
“…It is however of interest that a translocationaffecting chromosome 20 in SOM 196 was rapidly lost from invasive variants, possibly targeting relevant genes on chromosome 20. It has been suggested that specific genes on chromosome 20 may play a role in allowing cultured cells to bypass senescence [17]. Immortalisation of human uroepithelial cells with human papillomavirus 16 (HPV 16) E7 is associated with non-random accumulation of chromosome 20 material, either by low level gain of chromosome 20q, or amplification of 20q13.2, suggesting the presence of a dominant immortalising gene on chromosome 20.…”
Section: Discussionmentioning
confidence: 60%
“…It is however of interest that a translocationaffecting chromosome 20 in SOM 196 was rapidly lost from invasive variants, possibly targeting relevant genes on chromosome 20. It has been suggested that specific genes on chromosome 20 may play a role in allowing cultured cells to bypass senescence [17]. Immortalisation of human uroepithelial cells with human papillomavirus 16 (HPV 16) E7 is associated with non-random accumulation of chromosome 20 material, either by low level gain of chromosome 20q, or amplification of 20q13.2, suggesting the presence of a dominant immortalising gene on chromosome 20.…”
Section: Discussionmentioning
confidence: 60%
“…The gain of chromosome 20 observed in all the immortalized cell line is indeed intriguing. Low copy number gain of chromosome 20 has previously been reported to be associated with cellular immortalization by viral oncoproteins and hTERT [44][45][46][47]. These results suggest that the gain of this chromosome might contribute to immortalization.…”
Section: Discussionmentioning
confidence: 98%
“…Other than chromosome 20q gain per se, this amplification was associated with genomic instability, despite retention of wild-type p53 [23]. Interestingly, both 20q gain and 20q13.2 amplification have been reported for various cancer types [33] including UC [34–36], where amplifications of chromosome 20q generally appear to be associated with immortalization, oncogenic transformation and malignant progression. Whereas high level amplifications correlated with tumor progression in breast cancer [37], low-level amplifications appeared to be rather associated with early stage ovarian carcinoma [38].…”
Section: Discussionmentioning
confidence: 99%